The part-time soul : case studies in the management of culture and flexibility in Irish retail - Tormey, Roland (Trinity College (Dublin, Ireland). Department of Sociology, 2000)
Post-modem organisational analysis claims to have identified a post-modern organisational form. This new organisational form is alleged to be non-bureaucratic, flexible, opaque in organisation and to involve the management of culture and identity. This research project assessed the likelihood that such organisational forms could exist by looking at potential conflicts between different aspects of such an organisational form. The question which this research set out address was: what is the interaction between the management of culture and the management of flexibility in commercial organisations? It is possible to identify two ways in which different types of flexibility may limit the capacity of a company to manage culture. On one hand, the mobilisation of certain types of flexibility is likely to give rise to changes in the material situation of a firm’s employees. This may mean shorter or different working hours, or less take home pay. Whether or not this can be reconciled with the management of culture is not something that can simply be asserted (as the post-modernists do) or denied (as the materialists do).
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin